Evaluation of an alternative transport initiative in Perth, Western Australia 2000-2004 - McManus, Alexandra; Smith, Jennifer; McManus, J.; MacDonald, E.; Williams, M. (Australian Health Promotion Association, 2005)
Issue addressed: Perth Western Australia, has the highest proportion of per capita car ownership in Australia. Despite the various health, environmental and traffic-related benefits, the uptake of alternative forms of transportation such as walking, cycling and public transport are low.Methods: In response to a growing reliance on motorised transport, the Department for Planning and Infrastructure's (DPI's) Cycling Unit conducts an annual Bike to Work Breakfast to promote cycling as a viable form of transport to work. During this event a short cross sectional survey is distributed to assess the usual cycling behaviours of attendees. Topical issues relating to cycling are also investigated.Results: Results from the 2004 survey indicated that the majority of respondents cycled at least 2-3 times per week (85%) to improve fitness (88%), for enjoyment (70%) and because it was a cost effective means of transport (45%). Most of the respondents (92%) supported the need for more cycle friendly infrastructure such as advanced stop lines at intersections and safety measures such as wearing cycle helmets (85%). These findings were consistent with results from similar surveys conducted between 2000 and 2003.Conclusions: The DPI's Bike to Work Breakfast is a popular event within the cycling calendar that provides the opportunity to gain a snapshot of cycling behaviours and attitudes of cyclists. Prior consultation with the evaluators in the developed of the survey instrument has the potential to investigate barriers and enablers to cycling on a regular basis. Age and gender differences could also be explored.